A corpus-based study on contrast and concessivity of the connective -ciman in Korean - Lee, Hye Kyung (Pragmatics, 2022)
Providing a corpus-based analysis of the contrastive connective -ciman in Korean, this study demonstrates that global connections are as frequent as local connections as opposed to previous literature. In representing various senses possible with a -ciman connection, this study adopts a fuzzy representation, where meanings range from conceptual to discoursal. The identified meanings include explicit contrast, denial of expectation, speech act hedges and idiomatic expressions. The fuzzy representation is supported for at least two reasons. First, categorization of some cases is often blurred. Second, it can better capture the relatedness of various meanings whose enduring sense concerns ‘contrast’. It is further revealed that interpretations of -ciman phrases are compositionally made with co-occurring linguistic units. The “pragmatic” meanings of -ciman constructions are explained in terms of different levels of representations in which the contrast occurs. We further investigate the possibility of -ciman as a stance/discourse marker with accompanying expressions.
Keywords: -ciman; Concessivity; Contrast; Fuzzy representation; Korean; Stance marker